Characterization of an MLC patient carrying two MLC1 variants showing radiological improvement - Clara Mayayo-Vallverdú; Laura Ferigle; Marta Vecino-Pérez; Julián Lara; Virginia Nunes; Raúl Estévez (Brain Disorders, 2023)
Megalencephalic leukoencephalopathy with subcortical cysts (MLC) is a rare type of vacuolating leukodystrophy. Approximately 75% of MLC patients have variants in MLC1, while the rest in GLIALCAM, GPRC5B and AQP4. From the GLIALCAM patients, a classical and a benign phenotype can be distinguished, in which a recessive and dominant inheritance is observed, respectively. Here, we report a new MLC patient harboring two variants in MLC1 with radiological improvement. The patient is heterozygous for the variants c.597+37C>G and c.895–1G>T affecting both mRNA splicing, and the latest causes the deletion p.Pro299_Glu353del. By analyzing mRNA and protein obtained from patient's peripheral blood leukocytes, we could demonstrate the expression of a small amount of wild-type MLC1 mRNA and protein in the patient. Thus, we suggest that the improvement of clinical and radiological abnormalities observed in all remitting MLC patients might be due to the presence of residual amounts of MLC1 protein.